Penurunan Kekuatan Tarik Rantai Elastomerik Sintetis pada Retraksi Kaninus - Ratna Indrati (Faculty of Dentistry, Universitas Indonesia, 2015)
The synthetic elastomeric chain (S.E.C) is one of the current most popular orthodontic accessory. There are many variance brands, types and colours available at the dental market. The alternative funtion of the chain is facilitates canine retraction. S.E.C is applied by stretching it to a certain distance, so it would be able to produce a certain needed force strength. S.E.C is made of polymer polyurethane, which is not recognizable as an ideal elastic material. The polymer is subjected to change its utilization. Researchers had showed that the declining of S.E.C force strength depends on its brand type, colour and the length of the stretching force. Further, a S.E.C of the same brand, type and colour might not produce and deliver the same initial force strength. Research studies reported that the optimal force applied for retracting canine without generating the destruction of periodontal ligament ranges 55-300 g.